KEMAMPUAN PREDIKTIF EARNINGS DAN ARUS KAS DALAM MEMPREDIKSI ARUS KAS MASA DEPAN* - DAHLER, YOLANDA; FEBRIANTO, RAHMAT (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 2 No 2 (2007))
The objective of this study is to investigate whether earnings or operatingcash flows have more predictive ability to predict future operating cash flowsbetween firms reporting positive profit and firms reporting negative profit.Although prior study indicates a strengthening relationship between earnings andfuture operating cash flows for both firms reporting profits and losses, whilerelationship between current and future operating cash flows is neither increasingnor decreasing, our result indicates that both earnings and cash flows have abilityto predict future operating cash flow for firms reporting positive profit. On theother hand, for firms reporting negative profit, earnings are not significant topredict future operating cash flows while current operating cash flows still haveability to predict future operating cash flows.
Keywords: earnings, current operating cash flows, future operating cash flows, firms reporting positive profit, firms reporting negative profit